Identification of a heat-shock protein promoter and construction of a novel stress inducible Lactobacillus-lactococcus shuttle vector - Thakib Maidin, Mohd Shawal (2013)
Lactic Acid Bacteria (LAB) have been long established as a consortium of bacteria with high economic value. Among the sub-species of LAB, Lactobacillus plantarum and Lactococcus lactis are the two most studied and widely commercialised. This includes their applications such as being used as starter culture in fermentation industries, vaccine development and metabolite production. In addition, these LABs have been genetically engineered because of their small genomes, easy genetic accessibility and the availability of genetic tools. However, there is still a lack of available shuttle vectors with strong promoter and broad host range for these two species of LAB. In addition, other promoters except for the nisin promoter are also less efficient. A new promoter inducible by stress may offer several advantages such as ease of gene expression, low cost and broad host range compatibility. In this study, bacteria containing plasmid was screened and identified as Enterococcus faecium HB6. The plasmid was characterised and named as pAR6. Three putative open reading frames (ORF) coding for the epsilon antitoxin, small heat shock protein and replication were identified. The small heat shock protein promoter (Phsp) was characterised and cloned into lactococcal promoter screening vector, pNZ8008. The quantitative expression analysis of Phsp under various stress conditions showed that the maximum gusA (β-glucuronidase) activity was achieved under a stress combination of heat at 37°C, media with salt concentration of 3% (w/v) and alkalinity of pH9. A new Lactobacillus-Lactococcus shuttle vector pAR1801 was constructed by ligating the cassettes between a previously isolated Lactobacillus plasmid, pR18 containing the mob, sso, dso, repA and terminator sequence with Lactococcus pNZ8048-Phsp vector, containing the chloramphenicol resistant gene,enterococcal Phsp replaced lactococcal Pnis, multiple cloning site and terminator site.The shuttle vector was transformed into Lb. plantarum Pa21 and L. lactis NZ9000 hosts and was stably maintained until 50 generations. Results from relative qPCR determined that the copy number of the plasmid vector pAR1801 in Lb. plantarum Pa21 and L. lactis NZ9000 hosts were 34 and 31 copies per cell respectively. The functionality of pAR1801 to carry and express foreign genes was tested using the gusA gene. The pAR1801-GUS recombinant plasmid was transformed into both hosts, and was able to replicate and express the gusA gene as was shown by the ability of the cells to hydrolyse the X-Gluc (5-bromo-4-chloro-3-indolyl glucuronide). In conclusion, a hsp promoter was cloned and a functional stress inducible Lactobacillus and Lactococcus shuttle vector was constructed.